(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article explores the significance of modern pedagogical technologies in the teaching of the fundamentals of nursing science. It delves into the literature to analyze existing research on this topic, investigates various methods employed, presents results, engages in discussion, and draws conclusions with suggestions for future directions in nursing education.